PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE PERUSAHAAN BUMN - Shella Oktavia Lee; Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The objective of this research is to obtain empirical evidence about the effect of good corporate governance which include audit committee, board size, independent commissioner and intellectual capital on financial performance in state-owned enterprises listed on the Indonesia Stock Exchange (IDX) during the year 2015-2019. This study uses secondary data. This research is conducted with a sample of 59 state owned enterprises data with the technique used in this study is purposive sampling. The research data was processed using Statistical Product and Service Solution software for Windows version 23 (SPSS version 23). The results of this research show that the intellectual capital and independent commissioner have a significant influence on financial performance, while audit committee and board size do not have a significant effect on financial performance. The implication of this study is the need to increase the role of audit committee, board of directors and independent commissioner to increase good corporate governance and manage intellectual capital that will increase the firm financial performance.